MAKNA HOLISTIK TARI KETHÈK OGLÈNG KARYA GUNTUR TRI KUNCORO - Firdauzhi Nuzulla Mustika Prismadianto; Maryono Maryono (Institut Seni Indonesia Surakarta, 2021)
This writing aims to reveal the meaning of the Kethek Ogleng dance by Guntur Tri Kuncoro by examining the problems formulated, namely the concept of the emergence of the Kethek Ogleng dance, the form of the Kethek Ogleng dance, the audience's response, and the meaning of the Kethek Ogleng dance by Guntur Tri Kuncoro. The analysis uses a holistic art criticism approach that is based on three main factors, namely genetics related to the concept of the appearance of the work, objective in the form of works and affective as a response or emotional response of the audience who are all sources of value flow. The form of writing is qualitative with data collection strategies through: observation, interviews and literature study. The results show that holistically the Kethèk Oglèng dance is meaningful as an entertainment medium, as a promotional event for cultural tourism, and is expected to be used as a means of student education and as an icon or identity of the City of Kediri.